Vanadium Compounds as Biocatalyst Models. - Parente, Juliana Elena (2020)
Peroxidovanadium(V) and oxidovanadium(IV) compounds have been tested as peroxidase-similar compounds. Their catalytic performance was tested on phenol red and pyrogallol substrates. Bromination kinetic studies revealed Michaelis-Menten behavior with respect to phenol red for both complexes. Catalytic efficiency is ~ 104M−1 min−1. Both vanadium complexes showed the capacity to oxidize pyrogallol, but only the oxidovanadium(IV) complex follows Michaelis-Menten kinetics with respect to this substrate (Km = 1.05 × 10-3 M). Peroxidovanadium(V) complex displayed a more complex mechanism, and further studies became necessary to elucidate it. The structure-activity relationship was also assessed.